ADV6209 for Premedication in Pediatric Anesthesia: A Double-Blinded, Randomized Controlled Trial - Markus Zadrazil; Peter Marhofer; Werner Schmid; Daniela Marhofer; Philipp Opfermann (MDPI AG, 2022)
ADV6209, a new formulation of midazolam with the addition of γ-cyclodextrin for oral use, has recently been licensed as the first pediatric sedative in the European Union. We compared the clinical efficacy of ADV6209 to the standard formulation of midazolam in premedication to reduce anxiety in children before anesthesia induction in a randomized, double-blinded controlled trial. Eighty children (ASA I/II; age: 2-8 years) scheduled for elective surgery were randomized to receive 0.25 mg kg−1 of either conventional midazolam or ADV6209. Assessment tools included the modified Yale Preoperative Anxiety Scale-Short Form (mYPAS-SF) as well as scores for oral acceptance of the premedication and facemask acceptance during inhalational anesthesia induction. Mann-Whitney U and Pearson's chi-square tests were used for comparisons of outcome parameters. The primary outcome parameter of the study (mYPAS-SF anxiety score 30 min after the drug administration) did not reveal any significant intergroup difference between the ADV6209 group and the conventional midazolam group. Both drugs revealed their efficacy in reducing anxiety and in providing adequate sedation. The premedication dose was accepted by all children in the ADV6209 but rejected by 15% in the conventional midazolam group (p = 0.037). Acceptance of facemask placement was not found to differ significantly. No adverse events related to the study medications were noted. ADV6209 was better orally accepted than the conventional midazolam preparation and proved its efficacy in reducing preoperative anxiety. This clinically interesting preparation may alleviate the premedication process of 2−8 year-old children and obviates off-label drug use.